Peningkatan dan Standarisasi Mutu Pendidikan: Tinjauan atas UU, Kurikulum dan Kemampuan Guru - Muzhoffar Akhwan (Islamic University of Indonesia, 2003)
The paradigm of education in future is democracy. In Indonesia after the Era of Reformation there were big changes in the policy of education, for example school based management and competency based curriculum since 2001. Therefor to develop the curriculum it is must to do reformation and reorientation to the system of education.Thus, efforts to strengten the capability of those teachers to became professional educators were unavoidable. Because, the role of teachers in establishing new geration and civilization in the mids of global changes are very significant. Change the curriculum of education from centralistic to decentralization and change the curriculum of education from theoretic oriented to problem oriented; how the teacher deliver subject of teaching from the real problem faced by students with constructivist approach.